Takaful claim dilemma - Yakob, Rubayah; Redzuan, Hendon; Janor, Hawati (2015)
“What a long and tedious meeting!” Borhan was heard grumbling.He had just finished attending July monthly meeting with the top management of Takaful Dinamik Berhad (TDB), a takaful company located in the heart of Kuala Lumpur.Just as he was about to breathe a sigh of relief, Borhan saw a letter which was discreetly placed on his table by his secretary.He was about to throw his files onto the letter when his eyes caught the phrase "Bank Negara Malaysia” (BNM) on the letter.BNM is the Central Bank of Malaysia and responsible for regulating and monitoring the insurance and takaful industry in the country. Borhan felt a bit anxious. With a furrowed brow he opened the letter and scrutinized the content line by line.